Analisis Efektivitas Penerapan Sistem E-Bphtb Pada Badan Pendapatan, Pengelolaan Keuangan Dan Aset Daerah Kabupaten Magelang Bagian Pelayanan - Angga Adhinata Amrulloh; Maulidyati Aisyah (Jurnal Manajemen Riset Inovasi, 2024)
Land and Building Rights Acquisition Fee (BPHTB) is a tax imposed on the acquisition of land and/or building rights. BPHTB payments in Magelang Regency require validation from BPKAD to be used as a condition for the process of transferring rights to land and buildings. The validation process usually takes quite a long time. This requires a special strategy to increase regional tax revenues in Magelang Regency. This research uses qualitative methods, namely data collection techniques through observation, interviews and documentation. The results of this research provide information that has been carried out by BPPKAD Sleman Regency to maximize regional tax revenues by developing the E-BPHTB system, so that the regional tax collection process is easier and faster. However, the problems in using the new system are still unfamiliar, so time is needed to adapt to using the system.